The Architectural Design of a Sports Facility in Asahan Regency with a Tropical Architecture Approach - Azizur Rohman Nasution; Melly Andriana (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This design project is motivated by the low public interest in sports and the limited availability of sports facilities, creating a need for a sports hall that is both effective and efficient in enhancing the community’s quality of life. However, the mere provision of a sports facility is not sufficient; considerations such as building orientation, opening design, and airflow circulation are essential to create an optimal environment for sports activities. Therefore, the tropical architecture approach serves as the primary design basis for the sports hall in Asahan Regency. The aim of this design is to support a healthy lifestyle and improve the quality of life of the local community through comfortable and safe sports activities. The design method adopts a qualitative approach, with data collected through interviews and field observations to understand the needs and preferences of the community. The design also reflects local identity through a mass transformation inspired by the shell form, symbolizing the city of Asahan. The shell structure system is known for its slenderness, making it lightweight and efficient, while its curvature ensures even load distribution. This approach can serve as a model for future sports facility developments in Asahan Regency. This sports hall is expected to become a central hub for athletes in Asahan, providing optimal training facilities to improve their performance. With a modern building and complete facilities, the community can engage in sports activities more comfortably and safely, thus increasing public interest in sports and enhancing overall well-being. This design also aims to promote awareness of the importance of a healthy lifestyle through an effective and efficient sports center.